2007
DOI: 10.1016/j.mce.2006.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of HPA axis homolog in the skin

Abstract: SummaryHuman skin expresses elements of the hypothalamo-pituitary-adrenal (HPA) axis including proopiomelanocortin (POMC), corticotropin releasing hormone (CRH), the CRH receptor-1 (CRH-R1), key enzymes of corticosteroid synthesis and synthesizes glucocorticoids. Expression of these elements is organized in functional, cell type-specific regulatory loops, which imitate the signaling structural hierarchy of the HPA axis. In melanocytes and fibroblasts CRH-induced CRH-R1 stimulation upregulates POMC expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
269
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 258 publications
(283 citation statements)
references
References 83 publications
(173 reference statements)
13
269
0
1
Order By: Relevance
“…Because P450scc is expressed in the gut where it plays a role in local corticosteroid production (FernandezMarcos et al, 2011), it could play a role in first-pass metabolism of ergosterol before it reaches the liver for excretion. Furthermore, P450scc is expressed in several other extra-adrenal and extragonadal tissues including skin, where it serves as a starting point for local steroids synthesis (Slominski et al, 2004(Slominski et al, , 2007, metabolizes 7-dehydrocholesterol (animal equivalent of plant ergosterol) , or potentially may play a role in nonclassic vitamin D metabolism (Slominski et al, 2005a(Slominski et al, , 2011. Thus, when topically applied, ergosterol may serve as a substrate for P450scc with potential implications in therapy of skin hyperproliferative or inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Because P450scc is expressed in the gut where it plays a role in local corticosteroid production (FernandezMarcos et al, 2011), it could play a role in first-pass metabolism of ergosterol before it reaches the liver for excretion. Furthermore, P450scc is expressed in several other extra-adrenal and extragonadal tissues including skin, where it serves as a starting point for local steroids synthesis (Slominski et al, 2004(Slominski et al, , 2007, metabolizes 7-dehydrocholesterol (animal equivalent of plant ergosterol) , or potentially may play a role in nonclassic vitamin D metabolism (Slominski et al, 2005a(Slominski et al, , 2011. Thus, when topically applied, ergosterol may serve as a substrate for P450scc with potential implications in therapy of skin hyperproliferative or inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cholesterol, a precursor from which steroid hormones are synthesized, is produced by skin (31). All major components of HPA axis (CRH, CRH-R, urocortin, POMC, ACTH, MC-R) and critical enzymes necessary for GCs synthesis are produced and identified in skin (32)(33)(34)(35)(36). In addition, isolated hair follicles, dermal fibroblasts, and melanocytes secrete cortisol and display HPA axis-like regulatory feedback systems (37)(38)(39).…”
mentioning
confidence: 99%
“…HF immune privilege, connective tissue sheath (CTS) mast cell degranulation. (see Arck et al, 2005a; Bodó et al, 2005 and2007; Botchkarev et al, 2004; Colombe et al., 2007; Deplewski and Rosenfield, 2000;Hasse et al, 2007; Kauser et al, 2006;Ohnemus et al, 2006;Paus et al, 2006;Peters et al, 2006b and2007;Philp et al, 2004;Slominski et al, 2007;Telek et al, 2007;Zouboulis et al, 2007) While this remains to be conclusively demonstrated, it is likely that HFeSC are fully integrated into this neuroendocrine tapestry of general HF biology. However, all we have to go by currently are some pointers to potentially important elements in the as yet obscure neuroendocrinology of HFeSC.…”
mentioning
confidence: 99%
“…It now needs to be characterized whether human and/or mouse HFeSC in the bulge express constitutively higher or lower levels of receptors for classical secreted stress mediators e.g. CRH, ACTH, NGF, substance P, prolactin and cortisol) -all of which are synthesized in the human HF itself (Peters et al, 2006 a;Slominski et al, 2007). Also, in view of the observation that these cells appear to fail to show appropriate desensitization responses to glucocorticoid stimulation (Chebotaev et al, 2007) one needs to know how HFeSC respond to stimulation with these neuron-endocrine stress mediators.…”
mentioning
confidence: 99%